Telipogon crisariasae (Orchidaceae) a new species from northen Ecuador - Baquero R., L.E.R.; Iturralde, G.A.; Martel, C. (Magnolia Press, 2022)
Telipogon crisariasae, discovered in northern Ecuador, is described as a new species. Telipogon crisariasae is similar to T. octavioi but differs by its larger inflorescences and flowers, the rhomboid petals, the cordiform pink callus, and the sub-trapeziform stigmatic cavity. Illustrations and pictures of the new entity are provided. Furthermore, diagnostic characters of T. crisariasae are compared to those of other morphologically similar species.
Keywords: Orchidaceae; Biology; Petal; Inflorescence; Botany; Taxonomy (biology); https://purl.org/pe-repo/ocde/ford#1.06.03